Analysis of the polyhedrin gene promoter of the Autographa californica nuclear polyhedrosis virus. - Possee, R D (1987)
The polyhedrin gene promoter of the Autographa californica nuclear polyhedrosis virus was analysed with respect to which sequences are required upstream of the mRNA transcription initiation (CAP) site for efficient promoter activity. Insertions (8, 95 and 785 nucleotides) were made in this region at an EcoR V site between the CAAT- and TATA-like boxes. When these mutations were introduced into the virus they did not affect the activity of the polyhedrin promoter as judged by expression of the beta-galactosidase (lacZ) gene inserted in lieu of the polyhedrin coding sequences. Deletions were made in the promoter which progressively removed sequences upstream from the CAP site. Removal of the TATA motif did not affect lacZ gene expression. A sequence 69 nucleotides upstream to the normal position of the polyhedrin ATG translation initiation codon was sufficient for maximum promoter activity but this was reduced by 90% when only 56 nucleotides upstream remained. The normal CAP site was utilized by each deletion mutant. Promoter activity was undetectable when the CAP site was deleted. The results are discussed in relation to other eukaryotic promoters.